2022
DOI: 10.1039/d2sc04207j
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the frontier orbitals of L(X)Ga-substituted diphosphenes [L(X)GaP]2(X = Cl, Br) and their facile oxidation to radical cations

Abstract: Modulating the electronic structures of main group element compounds is crucial to control their chemical reactivity. Herein we report on the synthesis, frontier orbital modulation, and one-electron oxidation of two...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 108 publications
5
7
0
Order By: Relevance
“…2 crystallizes in the monoclinic space group P 2 1 / n with one independent molecule and disordered solvent molecule ( n ‐hexane) in the asymmetric unit [17] . The short P1−P2 (2.0662(5) Å) and C30−C31 (1.399(2) Å) bonds within the planar P 2 C 2 π‐conjugated unit are comparable to other P−P and C−C double bonds [1d,e,8,15] and calculated values [18a] . The P2−C30 (1.7919(14) Å) bond length is also consistent with the sum of the calculated single bond radii (P 1.11 Å; C 0.75 Å), [18b] and the Ga1−P1 (2.2844(4) Å) and C31−N3 (1.3815(18) Å) bond lengths of 2 agree with experimental Ga−P [14,15] and C−N [1,8–10] single bonds, respectively.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…2 crystallizes in the monoclinic space group P 2 1 / n with one independent molecule and disordered solvent molecule ( n ‐hexane) in the asymmetric unit [17] . The short P1−P2 (2.0662(5) Å) and C30−C31 (1.399(2) Å) bonds within the planar P 2 C 2 π‐conjugated unit are comparable to other P−P and C−C double bonds [1d,e,8,15] and calculated values [18a] . The P2−C30 (1.7919(14) Å) bond length is also consistent with the sum of the calculated single bond radii (P 1.11 Å; C 0.75 Å), [18b] and the Ga1−P1 (2.2844(4) Å) and C31−N3 (1.3815(18) Å) bond lengths of 2 agree with experimental Ga−P [14,15] and C−N [1,8–10] single bonds, respectively.…”
Section: Resultssupporting
confidence: 86%
“…We recently showed that electropositive L(X)Ga substituents stabilize open‐shell and π‐bonded pnictogen compounds [11] and other unusual bonding situations [12] . Moreover, gallaphosphenes [13] were found to undergo cycloaddition and E−H (E = N, O, S, Se) bond activation reactions, [13,14] and carbene‐coordinated diphosphenes were oxidized to radical cations [15] . We report here the synthesis of LGa(P 2 OC)cAAC 2 (L = HC[C(Me)N(Ar)] 2 ; Ar = 2,6‐ i‐ Pr 2 C 6 H 3 ) with a 1,2‐diphospha‐1,3‐butadiene moiety, its radical anion 3 ⋅ − and the 1,2‐diphospha‐1,3‐butadiene anion 4 − .…”
Section: Introductionmentioning
confidence: 99%
“…2 crystallizes in the monoclinic space group P 2 1 / n with one independent molecule and disordered solvent molecule ( n ‐hexane) in the asymmetric unit [17] . The short P1−P2 (2.0662(5) Å) and C30−C31 (1.399(2) Å) bonds within the planar P 2 C 2 π‐conjugated unit are comparable to other P−P and C−C double bonds [1d,e,8,15] and calculated values [18a] . The P2−C30 (1.7919(14) Å) bond length is also consistent with the sum of the calculated single bond radii (P 1.11 Å; C 0.75 Å), [18b] and the Ga1−P1 (2.2844(4) Å) and C31−N3 (1.3815(18) Å) bond lengths of 2 agree with experimental Ga−P [14,15] and C−N [1,8–10] single bonds, respectively.…”
Section: Resultssupporting
confidence: 86%
“…The short P1−P2 (2.0662(5) Å) and C30−C31 (1.399(2) Å) bonds within the planar P 2 C 2 π‐conjugated unit are comparable to other P−P and C−C double bonds [1d,e,8,15] and calculated values [18a] . The P2−C30 (1.7919(14) Å) bond length is also consistent with the sum of the calculated single bond radii (P 1.11 Å; C 0.75 Å), [18b] and the Ga1−P1 (2.2844(4) Å) and C31−N3 (1.3815(18) Å) bond lengths of 2 agree with experimental Ga−P [14,15] and C−N [1,8–10] single bonds, respectively. The five‐membered GaP 2 OC heterocycle is coplanar with the P 2 C 2 π‐conjugated system, and the C 3 N 2 Ga metallacycle is perpendicular to this plane.…”
Section: Resultssupporting
confidence: 86%
“…Phosphorus-centered radicals are an important class of reactive intermediates that are involved in many chemical reactions . During the past decades, a variety of stable phosphorus-centered neutral, cationic, and anionic radicals have been isolated and structurally characterized. However, the isolation of stable phosphinyl [R 2 P] • radicals is still quite challenging due to their intrinsic high propensity to dimerize.…”
mentioning
confidence: 99%